Enhancement And Implementation Of GSM Networks In Malaysia: An Erricson Study - Mahboubi, Omid (2009)
Ericsson is the leading telecommunication company. This study is concerned about the depth general information of Ericsson and analyze the business environment and strategic planning of Ericsson.